Can Mini Grant Programs Address Community Health Improvement Plans in Rural Areas? A Local Evaluation - Kelley Ditzel; Cameron Watts (Georgia Southern University, 2022)
Background: In the rural community of Hancock County, Georgia, it became apparent in the summer of 2017 that outside help was necessary to address the failing health and education problems plaguing this area. The North Central Health District received Healthcare Georgia Foundation grant leading to the creation of the Hancock Health Improvement Partnership (HHIP) composed of 11 community leaders who developed the Community Health Improvement Plan to positively impact their county. Methods: This evaluation was conducted to report the efficacy of the mini grant program developed by the HHIP, particularly how grants could best improve organizational capacity, incentivize community collaborations, administer outcome evaluations, and support the sustainability of initiatives beyond grant funding. The following study provides an evaluation of several community-based mini grant programs informed by the many lessons learned from our experience with HHIP. A logic model was used to directly trace each grantee's work from initial inputs, to measurable outcomes, and finally paired those outcomes with the appropriate objective originally identified by community members. To account for the effects of the COVID-19 pandemic, results were based on qualitative representations of grantee's work. Results: The effects of the COVID-19 pandemic negatively impacted the quantitative analysis of specific outcomes. We pivoted to general measurements of reach demonstrated through a logic model and qualitative representations of grantee's work. While meaningful benefit is clear, organizational capacity and sustainability continue to be problematic for small, rural organizations. Conclusions: Mini grant programs are compatible with accomplishing the objectives of community-based improvement plans if certain guidelines are followed. Organizations designing mini grant programs for this purpose should recognize the importance of design and preparation to maximize the impact and sustainability of their efforts. Furthermore, rural communities should utilize their asset of collaboration and the synergy that occurs when everyone can work together.